Low-fat dietary pattern and global cognitive function: Exploratory analyses of the Women's Health Initiative (WHI) randomized Dietary Modification trial - Chlebowski, Rowan T. (EClinicalMedicine, 2020)
BACKGROUND: Meta-analyses of observational studies associate adherence to several dietary patterns with cognitive health. However, limited evidence from full scale, randomized controlled trials precludes causal inference regarding dietary effects on cognitive function. METHODS: The Women's Health Initiative (WHI) Dietary Modification (DM) randomized trial, in 48,835 postmenopausal women, included a subset of 1,606 WHI Memory Study (WHIMS) participants >= 65 years old, to assess low-fat dietary pattern influence on global cognitive function, evaluated with annual screening (Modified Mini–Mental State Examinations [3MSE]). Participants were randomized by a computerized, permuted block algorithm, stratified by age group and center, to a dietary intervention (40%) to reduce fat intake to 20% of energy and increase fruit, vegetable and grain intake or usual diet comparison groups (60%). The study outcome was possible cognition impairment (failed cognitive function screening) through the 8.5 year (median) dietary intervention. Those failing screening received a comprehensive, multi-phase cognitive function assessment to classify as: no cognitive impairment, mild cognitive impairment, or probable dementia. Exploratory analyses examined the composite endpoint of death after possible cognitive impairment through 18.7 years (median) follow-up. The WHI trials are registered at ClinicalTrials.gov:NCT00000611. FINDINGS: Among the 1,606 WHIMS participants, the dietary intervention statistically significantly reduced the incidence of possible cognitive impairment (n = 126; hazard ratio [HR] 0.59 95% confidence interval [CI] 0.38–0. 91, P = 0.01) with HR for dietary influence on subsequent mild cognitive impairment of 0.65 (95% CI 0.35–1.19) and HR of 0.63 (95% CI 0.19–2.10) for probable dementia (PD). Through 18.7 years, deaths from all-causes after possible cognitive impairment were non-significantly lower in the dietary intervention group (0.56% vs 0.77%, HR 0.83 95% CI 0.35 to 2.00, P = 0.16). INTERPRETATION: Adoption of a low-fat eating pattern, representing dietary moderation, significantly reduced risk of possible cognitive impairment in postmenopausal women. FUNDING: Several Institutes of the US National Institutes of Health.